2010
DOI: 10.1111/j.1471-4159.2010.06636.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations induced by ischemia in primary cultures of astrocytes: merging 13C NMR spectroscopy and metabolic flux analysis

Abstract: J. Neurochem. (2010) 113, 735–748. Abstract Disruption of brain energy metabolism is the hallmark of cerebral ischemia, a major cause of death worldwide. Astrocytes play a key role in the regulation of brain metabolism and their vulnerability to ischemia has been described. Aiming to quantify the effects of an ischemic insult in astrocytic metabolism, primary cultures of astrocytes were subjected to 5 h of oxygen and glucose deprivation in a bioreactor. Flux distributions, before and after ischemia, were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 66 publications
3
18
1
Order By: Relevance
“…In this pathological condition the inhibition of PPP by 6-AN reduces the cardiac damage [51]. In contrast, in the early brain postischemic phase, surviving astrocytes significantly increase the metabolic flux through glycolysis and PPP, to produce ATP and NADPH, which in this case reduces the oxidative damage [52].…”
Section: The Ppp In Cardiovascular Diseasesmentioning
confidence: 99%
“…In this pathological condition the inhibition of PPP by 6-AN reduces the cardiac damage [51]. In contrast, in the early brain postischemic phase, surviving astrocytes significantly increase the metabolic flux through glycolysis and PPP, to produce ATP and NADPH, which in this case reduces the oxidative damage [52].…”
Section: The Ppp In Cardiovascular Diseasesmentioning
confidence: 99%
“…Neurons then take up lactate through membrane-bound MCT-2, which is then converted to acetone by lactate dehydrogenase, and acetone is then metabolized aerobically via the citric acid cycle to produce energy. [5][6][7][8][9] Moreover, lactate is closely associated with glucose metabolism, but a correlation with dynamic metabolic changes remains unclear. In vivo glucose metabolism in the brain is evaluated by [ 18 F] fluorodeoxyglucose imaging.…”
mentioning
confidence: 99%
“…Normally, brain activities are primarily supported by energy produced from the aerobic metabolism of glucose. [1][2][3] In a physiologic state, 90%-95% of brain energy is consumed by neurons, but 80% of glucose use happens in astrocytes, which suggests that a glucose mesostate released by astrocytes is absorbed and used by neurons to support their high energy consumption. A study 4 has shown that during glucose metabolism in the brain, lactate is a carrier of energy and facilitates interaction between astrocytes and neurons.…”
mentioning
confidence: 99%